Assessing the Effectiveness of Sterile Males Releases in Mediterranean Fruit Fly Population Reduction by Molecular Techniques - Juan-Blasco, María; Argilés, Rafael; Jaques, Josep A.; Castanera, Pedro; Urbaneja, Alberto; Sabater-Munoz, Beatriz (2017)
Autocidal control of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), has become the cornerstone of area-wide integrated pest management programs in many countries. In this technique a critical point is the mating success of released sterile males which should contribute to reduce wild populations. Till this moment the evaluation of mating success is not performed regularly in area-wide programs, being used an indirect measure as the recapture ratio of sterile versus fertile males, to evaluate the success of the sterile insect technique. We present here a review of the state of the art in mating success evaluation including the application of a molecular tool, which allows the quantification of mating success of released sterile males, linked to the progeny reduction at different sterile males release ratios using different medfly hosts. Implications of these results on the efficacy measurement of an area-wide SIT program are discussed.